Обрядовість осіннього циклу на рівненському Поліссі - Ковальчук, Н. (Народна творчість та етнографія, 2006)
Based on the local traditions of the Rivnenske Polissya the author analyses ancient autumn holidays seasonal traditions and rites of Polishchyky as well as transformational processes of the folk culture of this calendar period.